PENGARUH PERENDAMAN JUS DAUN SALAM SYZYGIUM POLYANTHUM (WIGHT) TERHADAP KANDUNGAN ASAM LEMAK BEBAS, TOTAL VOLATILE BASES DAN ANTIOKSIDAN PADA TELUR ASIN ASAP - Putri Zulia Jati (Research Center University of Pahlawan Tuanku Tambusai, 2021)
Duck eggs are a source of animal protein that has a delicious taste, easy to digest and highly nutritious so that it is loved by many people. In addition, eggs are easily damaged by the length of the trade chain and the improper storage process. The processed form of duck eggs, which until now is the best known and most favored by the people of Indonesia, is salted eggs. This study aimed to determine the effect of soaking salted eggs in bay leaf juice (Eugenia polyantha Wight.) at different concentration levels on the content of free fatty acids (FFA), total volatile bases (TVB) and antioxidants in smoked salted eggs. The experimental design used in this study was a completely randomized design (CRD) consisting of 5 treatments with 4 replications. The treatments consisted of: P0= Duck eggs + 0% bay leaf juice, P1 = Duck eggs + 25% bay leaf juice, P2 = Duck eggs + 50% bay leaf juice, P3 = Duck eggs + 75% bay leaf juice, P4 = Duck eggs + 100% bay leaf juice. The results showed that the effect of using salted egg soaking in bay leaf juice (Eugenia polyantha Wight.) showed a very significant effect (P<0.01) on FFA, TVB and antioxidants. It was concluded that the addition of bay leaf juice with a concentration of 25 to 100% in smoked salted eggs was able to reduce the number of free fatty acids, reduce the content of total volatile bases (TVB) and increase antioxidant activity. The use of the best concentration of 100% bay leaf juice is the lowest FFA 0.10 (%), the lowest TVB 2.32 (mgN%) and the lowest antioxidant 88.59 (mg/g). Keywords: Salted Egg, Free Fatty Acid (FFA), Total Volatile Bases (TVB), Antioxidant